Proteomic profiling of iPSC and tissue-derived MSC secretomes reveal a global signature of inflammatory licensing - Margeaux Hodgson-Garms; Matthew J. Moore; Mikaël M. Martino; Kilian Kelly; Jessica E. Frith (npj Regenerative Medicine)
Abstract Much of the therapeutic potential of mesenchymal stromal cells (MSCs) is underpinned by their secretome which varies significantly with source, donor and microenvironmental cues. Understanding these differences is essential to define the mechanisms of MSC-based tissue repair and optimise cell therapies. This study analysed the secretomes of bone-marrow (BM.MSCs), umbilical-cord (UC.MSCs), adipose-tissue (AT.MSCs) and clinical/commercial-grade induced pluripotent stem cell-derived MSCs (iMSCs), under resting and inflammatory licenced conditions. iMSCs recapitulated the inflammatory licensing process, validating their comparability to tissue-derived MSCs. Overall, resting secretomes were defined by extracellular matrix (ECM) and pro-regenerative proteins, while licensed secretomes were enriched in chemotactic and immunomodulatory proteins. iMSC and UC.MSC secretomes contained proteins indicating proliferative potential and telomere maintenance, whereas adult tissue-derived secretomes contained fibrotic and ECM-related proteins. The data and findings from this study will inform the optimum MSC source for particular applications and underpin further development of MSC therapies.